Heterogeneous international agreements: If per capita emission levels matter - Andreas Lange (Fondazione Eni Enrico Mattei (FEEM), 2002)
This paper studies the incentives for international cooperation if (some) countries prefer a more equitable distribution of per capita emission levels. The impact of such an equity preference is analyzed first for a bilateral, and then for a multilateral environmental problem. We show that - contrary to the two-country-case - for the latter there is no uniform percentage reduction of emissions that makes all countries better off. Rather, equity oriented countries (for example developing countries) enter a coalition only if they do not have to reduce as much. While equity preferences improve upon the prospects of cooperation if countries are not too different with respect to their per capita levels, if countries differ largely in population size and per capita emissions, generally no coalition will be stable without restrictions on entry into or exit out of a coalition. In such a situation, equity-orientation does not improve upon the prospects for cooperation.
Keywords: C7; D63; H41; Q00; 330; international environmental negotiations; equity preference; coalition formation; per capita emission levels; Umweltabkommen; Luftreinhaltung; Klimaschutz; Verhandlungen; Koalition; Theorie; Welt